Design and self-diagnostics of cyberphysical control devices on SOC platform - Shkil, Alexander; Rakhlis, Dariia; Filippenko, Inna; Korniienko, Valentyn (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2023)
The subject of research in this article is models, methods, and procedures for designing and self-diagnosing automated models of logic control devices implemented in SoCs. The object of work is the procedures for automated design and diagnosis of digital devices on the SoC technology platform. The aim of the study is to develop models and procedures for designing and self-testing in the cycle of automated design of automatic logic control systems on the SoC technology platform, which will significantly increase the reliability of their operation. The article solves the following tasks: consideration of the procedures for interacting the processor core with programmable logic as part of the SoC; improvement of the procedures for designing and testing software and hardware systems based on SoC; further development of procedures for automated design, verification, and diagnosis of cyber-physical logic control systems using programming languages and hardware description languages; implementation of the procedure for hardware self-testing of control automata on the SoC technology platform. The following methods are implemented: synthesis of control automata based on graph models, implementation of control automata models in the C programming language using an automata template, diagnostic experiment by traversing the automata transition graph. Results achieved. Based on the analysis of the procedures for the interaction of the processor core and programmable logic on the selected SoC platform, a model of a cyber-physical logic control system was designed. The practical implementation was carried out on the basis of the Vivado/Vitis/Vitis HLS CAD toolkit. The method of hardware self-testing of control automata on the technological platform of SoC ZYNQ-7000 was implemented. Conclusions. The article analyzes the principles of designing embedded cyber-physical systems implemented in system-on-chip. The principles of building verification systems and embedded self-diagnostics of system-on-chip systems containing software and hardware are considered. The developed methods are tested on a model of a traffic light logic control device on the SoC FPGA platform of the ZYNQ-7000 family by Xilinx. The Moore's control automaton is implemented in the PL block in the C programming language, and the operational automaton is implemented in the PS block. During the organization of the self-diagnosis process, a non-destructive diagnostic experiment was performed by traversing all arcs of the transition graph, starting from the initial vertex. In this case, the tester was an operational automaton, the reference logic and time values of which were stored in the memory of the PS unit. Visual observation of the diagnostic experiment was carried out using the LED panel of the ZedBoard board.